Influences of reduction temperature on energy storage performance of paraffin wax/graphene aerogel composite phase change materials. (March 2023) - He, Miao; Xie, Dengdeng; Yin, Lian; Gong, Kaili; Zhou, Keqing
Abstract: It is well known that poor thermal conductivity, easy leakage in melting, and low fire safety will hinder the practical application of phase change materials (PCMs) in energy storage. In this work, a series of graphene aerogels with different reduction degrees were obtained by regulating the reaction temperature and then compounded with paraffin wax to form composite PCMs. Satisfactorily, the composite PCMs not only showed a considerably improved shape stability compared to pure paraffin wax, but also an improvement in thermal conductivity from 13.56% to 44.44% with the increase of reduction temperature. Besides, the composite PCMs exhibited promising thermal stability and flame resistance. The peak heat release rate of the composite PCMs decreased by 27.5%, 32.1% and 41.3% respectively as the reduction temperature increased. More importantly, the composite PCMs had outstanding photothermal conversion capability, and the temperature of the composite phase change material could rise from 20 ℃ to 63 ℃ after absorbing light for 4 min. Overall, the increase of the reduction temperature of graphene aerogel has an outstanding contribution to improving the energy storage performance and thermal properties of the composite PCMs. Graphical Abstract: ga1